The Role of Women in Improving Family Food Security in Keras Village, Diwek District, Jombang: Peran Perempuan dalam Meningkatkan Ketahanan Pangan Keluarga di Desa Keras Kecamatan Diwek Jombang - Qurratul Aini, Saffana; Arifah, Siti; Shelly Devanti, Vinna; Rejeki Aminingsih, Sri; Baskoro Aji, Bayu; Efendi, Utoyo; Masluki, Atiqhanum (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
This community service activity was carried out in Keras Village, Diwek District, Jombang with the aim of improving family food security by cultivating hydroponic plants, so that each family can strengthen food security through this activity. The method used in this activity is training and mentoring with the Participatory Rural Appraisal (PRA) approach, planning and policies in rural areas by involving the community. This service was carried out as one of the work programs to improve the community's ability to manage yards so that the results can not only be consumed but also be used as additional family income. Utilizing yards with hydroponic techniques is easy to apply in everyday life, by planting various types of agricultural vegetables using hydroponic techniques can meet the community's food needs. Keras Village is a pilot village for food security and its yards are classified as narrow yards, so the yards can be utilized by planting various types of hydroponic plants.